PENGARUH UKURAN PERUSAHAAN, INTENSITAS MODAL, PROFITABILITAS, DAN LEVERAGE TERHADAP KEAGRESIFAN PAJAK - Tavia Raya, Laura (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.10.TAHUN.2024, 2024)
The actions of business entities that intend to lower the tax burden payable and are often aggressive are commonly referred to as tax aggressiveness. In practice, business entities may engage in tax aggressiveness either legally or illegally. Tax aggressiveness can occur due to the influence of several factors within the company. This study aims to examine the effect of company size, capital intensity, profitability, and leverage on the level of tax aggressiveness in property and real estate industry companies listed on the Indonesia Stock Exchange from 2019 to 2022. The number of research sample was 104 samples selected by purposive sampling. The data used comes from financial reports accessed through the Indonesia Stock Exchange web and analyzed using multiple linear regression techniques. The findings in this study are capital intensity and profitability affect tax aggressiveness. Company size and leverage do not affect tax aggressiveness. This research implies that a high level of capital intensity and profitability can encourage companies to reduce their tax aggressiveness.